Analisis Spasial Determinan Kasus Demam Berdarah Dengue (DBD) di Kota Bandung: Studi Komparatif Model SAR, SEM, dan SARMA - Kamal, Shafnanda Aulia; Nurkarim, Wahidya (Seminar Nasional Official Statistics, 2025)
Dengue Hemorrhagic Fever (DHF) is the third leading cause of death from infectious diseases in Indonesia. West Java Province, as the second most populous province in the country, and Bandung City, the most densely populated city in the province, have recorded the highest number of DHF cases from 2021 to 2024. This study aims to analyze the determinants of DHF and compare the performance of three spatial models—SAR, SEM, and SARMA—in explaining the distribution of DHF cases at the sub-district level in Bandung City. The data used include the number of DHF cases and socio-demographic variables such as the number of households in slum settlements, total population, and population density, analyzed spatially. The results show that the SEM model is the most optimal, with the lowest AIC value (320.881) and statistically significant spatial dependence in the residuals (p-value = 0.00352). Significant variables in the model include the number of households in slum areas, total population (log-transformed), and population density. These findings highlight the importance of spatial approaches in addressing DHF and support area-based health policies through coordinated cross-sub-district interventions.